ATM Kinase-Dependent Regulation of Autophagy: A Key Player in Senescence? - Stagni, Venturina; Ferri, Alessandra; Cirotti, Claudia; Barilà, Daniela (Frontiers in Cell and Developmental Biology, 2021)
In the past few years, our understanding of the interplay between autophagy and genomic stability has greatly increased. Recently, several papers suggest a molecular connection between the DNA Damage Response (DDR) and autophagy and explore how this link influences cell fate and the choice between senescence and apoptosis in response to different stimuli. The aberrant deregulation of this interplay is linked to the development of pathologies, including cancer and neurodegeneration. Ataxia-telangiectasia mutated kinase (ATM) is the product of a gene whose mutation leads to the development of a rare genetic disorder, Ataxia-Telangiectasia (A-T) characterized by cerebellar neurodegeneration, premature aging, defects in the immune response, and higher incidence of lymphoma development. Importantly, ATM kinase plays a central role in the DDR and it can finely tune the balance between senescence and apoptosis: activated ATM promotes autophagy and in particular sustains the lysosomal–mitochondrial axis, which in turn promotes senescence and inhibits apoptosis. Therefore, ATM is the key factor that enables cells to escape apoptosis by entering senescence through modulation of autophagy. Importantly, in contrast to apoptotic cells, senescent cells are viable and have the ability to influence cellular environment by secretion of pro-inflammatory and mitogenic factors. In this review we aim to summarize recent advances in understanding the molecular mechanisms linking DDR and autophagy to senescence, pointing out the role of ATM kinase in these cellular responses. The significance of this regulation in the pathogenesis of Ataxia-Telangiectasia will be discussed.